REVITALISASI RADIO LOKAL KOTA METRO LAMPUNG SEBAGAI MEDIA PENDIDIKAN PERSPEKTIF INDUSTRI MEDIA - Kuliyatun Kuliyatun (AT-TAJDID, 2017)
The function of mass mediacommunity has not run balanced.Especially with regard to social control and provide information regarding the importance of education to the general public.Local media in Metro Lampung has not been seriously considered as a comprehensive educational media. In fact, the mass media has a function to educate, entertain, inform, and as social control.The question in this article, how to revitalize the local SSB radio 92.1 FM in Kota Metro Lampung as educational media perspective Media Industry ?. This paper uses the theory of Industry(Branston dan Stafford: 2018-261).As the local media in Metro Lampung should be revitalized as a medium of education, through partnerships with LSM, foundations, private companies and others in order to obtain lucrative advertising.Local media industry has potential as a learning medium that is comprehensive and easily accepted by society. In educational institutions so that policies can be transferred effectively and efficiently in the community.Keyword: Local Radio, EducationMedia, Media Industry